The Effectiveness of Digitalization in Family Caregiver Empowerment Model (FCEM) for Reducing Diabetes Incidence in Rural Areas: An App-Based Literature Review Study - Fahmi Wildana; Lutfian Lutfian; Aufa Azizah; Izdihar Javier Wardika; Fariza Barika Ramadhani; Wahyu Dwi Utomo (Jurnal Ilmiah Kesehatan)
Diabetes mellitus (DM) is a condition characterised by anomalies in insulin production,